Combined Herbal Eye Drops Exhibit Neuroprotective and Intraocular Pressure-Reducing Effects in a Glaucoma Rat Model - Tibor Rak; Evelin Patko; Edina Szabo; Alexandra Vaczy; Dorottya Molitor; Dora Reglodi; Adrienne Csutak; Tamas Atlasz (Antioxidants)
(1) Background: Glaucoma is a multifactorial group of diseases characterized by progressive optic neuropathy. Intraocular pressure (IOP) is the only successfully modifiable risk factor for all forms of glaucoma. However, recent research has highlighted the reduction of oxidative stress and neuroinflammation as promising therapeutic targets. In this study, we evaluated the antiglaucomatous effects of a combined herbal extract applied as eye drops in a rat model of glaucoma. (2) Methods: Sprague Dawley rats were divided into four groups: healthy controls, glaucomatous animals treated with preservative-free artificial tears, and healthy and glaucomatous groups receiving combined herbal-based eye drops for 8 weeks. Glaucoma was induced through injection of microbeads into the anterior chamber at week 1 and week 3. Before the first injection and at weeks 4 and 8, rats underwent optical coherence tomography (OCT) and electroretinogram (ERG) recordings. Retinal analyses were conducted to assess retinal ganglion cell (RGC) count, vessel density, and markers of neural pathways, oxidative stress, and inflammation. (3) Results: The combination of herbal extracts showed beneficial effects on IOP elevation, and significantly improved ERG responses. Neuroprotective effects were assessed using OCT, immunohistochemistry, and proteomics. Most parameters in herbal eye drop-treated rats were not statistically different from those in healthy controls. (4) Conclusions: Topical administration of plant-based compounds may serve as an effective supportive therapy for ocular hypertension and retinal neuroprotection.